Carbon xerogel as catalytic support for noble metal based selective hydrogenation reactions - Machado, Bruno (2010)
Nitric acid treated carbon xerogel was used as support to prepare Pt, Ir and Ru monometallic catalysts. The introduction of oxygen surface groups was important to increase metal dispersion but proved to limit selectivity to cinnamyl alcohol during the hydrogenation of cinnamaldehyde. After an activation treatment to remove unwanted surface groups, Pt catalysts exhibited the highest selectivity, 73%, followed by Ir with 65% and finally Ru with only 32% (measured at 50% conversion).